Developments in the efficiency of the Malaysian banking sector: the impacts of financial disruptions and exchange rate regimes - Sufian, Fadzlan; Habibullah, Muzafar Shah (Sage Publications, 2012)
In the mid-1990s, East Asian countries have experienced severe fi nancial crisis that were followed by deep economic downturns. A variety of methodologies have been used to explain the Asian fi nancial crisis. However, the impact of the Asian fi nancial crisis of 1997 on the efficiency of the banking sector has not been studied yet. The present article attempts to provide new empirical evidence on the effi ciency of the Malaysian banking sector around the Asian fi nancial crisis. The efficiency estimates of individual banks are evaluated by using the non-parametric data envelopment analysis (DEA) method. The results indicate that the foreign banks have exhibited higher technical efficiency compared to their domestic bank counterparts. However, the results suggest that the foreign banks were severely affected by the Asian financial crisis, implying that the foreign banks are not insulated from unexpected events like the Asian financial crisis of 1997.